2002
DOI: 10.1590/s0100-879x2002001200005
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric connections between primary visual areas: beyond the midline rule

Abstract: In the last five years, a number of detailed anatomical, electrophysiological, optical imaging and simulation studies performed in a variety of non-human species have revealed that the functional organization of callosal connections between primary visual areas is more elaborate than previously thought. Callosal cell bodies and terminals are clustered in columns whose correspondence to features mapped in the visual cortex, such as orientation and ocularity, are starting to be understood. Callosal connections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…In humans, it consists of 铣200 million axons, making it the largest fiber tract within the CNS (Funnell et al, 2000;Houzel et al, 2002). It integrates information from the right and left hemispheres, and enables numerous complex brain activities (Mihrshahi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it consists of 铣200 million axons, making it the largest fiber tract within the CNS (Funnell et al, 2000;Houzel et al, 2002). It integrates information from the right and left hemispheres, and enables numerous complex brain activities (Mihrshahi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hemispheric interaction is critical for a unified representation of world (Houzel et al 2002), coordinating movement (Gerloff and Andres 2002), attentional processing (Banich 1998), pooling processing resources (Liederman 1998), and parallel processing (Compton 2002) among others. Bilaterally synchronous BOLD fluctuations have been previously observed in the motor cortex (Cordes et al 2000), visual cortex, thalamus, and hippocampus of humans (Stein et al 2000) and in the oculomotor and somatomotor areas of monkeys (Vincent et al 2007).…”
Section: Connectivity Patternsmentioning
confidence: 99%
“…It is possible that the corpus callosum is involved in more subtle mechanisms of depth perception than stereopsis (which is specifically defined as binocular disparity), such as relative motion or parallax, that is, using the differences in relative motion of near and far objects to judge depth (31). In this context, it has been suggested that visual callosal fibers participate in predicting trajectories of moving objects across the midline, and in the generation of binding mechanisms in the central visual field (19,20).…”
Section: Visual Callosal Fibers: Midline Fusion and Depth Perceptionmentioning
confidence: 99%
“…Furthermore, analyses of the morphology and diameter of callosal axonal branches suggest that the architecture of callosal axons is suitable to promote the synchronous activation of multiple targets in the opposite hemisphere (16). It would not be surprising that processes such as depth perception or binding in the central visual field depend on the generation of synchronous ensembles of neuronal activity in the two hemispheres, for which callosal fibers may be fundamental (20).…”
Section: Factors Favoring the Expansion Of The Corpus Callosum: Intermentioning
confidence: 99%